The violation of the cooperative maxim in early childhood: A pragmatic case study - Wini Tarmini; Nani Solihati; Somariah Fitriani; Nini Ibrahim (International Journal of Evaluation and Research in Education (IJERE), 2023)
The study examined the violation of the maxim of cooperation in early childhood conversation be means of a pragmatic case study, which is an important undertaking given the strong influence of the surrounding environment on children’s language development. Previous studies have delved into this area, particularly with regard to children with special needs, but have not widely explored how such a violation emerges in the early childhood period. Here, we adopted a qualitative approach using a pragmatic case study design, and over seven months collected data by observing, listening to and recording the conversations of a 4-year-old boy. The results of this process were used as transcripts for conversation data. Specifically, we found that of the 40 conversation data items concerning the form of cooperative maxim violations, there were 13 (32.5%) conversation data items. These results indicate that children in the early childhood period already possess pragmatic abilities, as evidenced by the ability to answer questions relevantly, but are constrained by their ignorance in answering questions correctly, thereby leading many children to violate the maxim of manners.